Two‐drug fixed‐dose combinations of blood pressure‐lowering drugs as WHO essential medicines: An overview of efficacy, safety, and cost. Issue 10 (20th August 2020) - Salam, Abdul; Huffman, Mark D.; Kanukula, Raju; Hari Prasad, Esam; Sharma, Abhishek; Heller, David J.; Vedanthan, Rajesh; Agarwal, Anubha; Rodgers, Anthony; Jaffe, Marc G.; R. Frieden, Thomas; Kishore, Sandeep P.
Abstract: Cardiovascular diseases (CVD) are the world's leading cause of death. High blood pressure (BP) is the leading global risk factor for all‐cause preventable morbidity and mortality. Globally, only about 14% of patients achieve BP control to systolic BP <140 mm Hg and diastolic BP <90 mm Hg. Most patients (>60%) require two or more drugs to achieve BP control, yet poor adherence to therapy is a major barrier to achieving this control. Fixed‐dose combinations (FDCs) of BP‐lowering drugs are one means to improve BP control through greater adherence and efficacy, with favorable safety and cost profiles. The authors present a review of the supporting data from a successful application to the World Health Organization (WHO) for the inclusion of FDCs of two BP‐lowering drugs on the 21st WHO Essential Medicines List. The authors discuss the efficacy and safety of FDCs of two BP‐lowering drugs for the management of hypertension in adults, relevant hypertension guideline recommendations, and the estimated cost of such therapies.